Pembinaan Penerapan Nomor Induk Berusaha dalam Mendukung Pengembangan UMKM Di Kelurahan Rungkut Kidul Surabaya - Zulkarnain Al Arsy, Muhammad; Khoirotunnisa, Fani (Education and Talent Development Center of Indonesia, 2025)
This community service program aims to provide assistance and education on the implementation of the Business Identification Number (Nomor Induk Berusaha or NIB) for Micro, Small, and Medium Enterprises (MSMEs) in Rungkut Kidul Sub-district, Surabaya. Many MSME actors in the area still lack formal business legality, which limits their access to government support programs such as funding, training, and partnerships. Through this initiative, the implementing team conducted socialization, technical training, and direct assistance in the online NIB registration process via the Online Single Submission (OSS) system. The method employed was a participatory approach, involving local business owners as active participants in each stage of the activity. The results indicate that most participants successfully obtained their NIBs and gained a better understanding of the importance of business legality for long-term development. This program has made a significant contribution by raising legal awareness and business capacity among the community, while also strengthening the foundation of the local economy through a more structured and formal MSME sector.